2023
DOI: 10.1109/access.2023.3250852
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Synthetic Biometrics: Fingerprint, Face, Iris and Vascular Patterns

Abstract: The research in this paper is a part of the joint project GENSYNTH (Tools for the Generation of Synthetic Biometric Sample Data). AMSL is funded in part by the Deutsche Forschungsgemeinschaft (DFG) under project no. 421860227. Wavelab is funded in part by the Austrian Science Fund (FWF) under project no. I4272.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Several studies indicate that the research focused on generating synthetic iris data is not as extensively explored as in other biometric modalities [1,11]. One of the earliest work in this field was conducted by Cui et al, using principal component analysis (PCA) for iris recognition and the super-resolution method for the synthesis.…”
Section: State Of the Art In Synthetic Iris Data Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicate that the research focused on generating synthetic iris data is not as extensively explored as in other biometric modalities [1,11]. One of the earliest work in this field was conducted by Cui et al, using principal component analysis (PCA) for iris recognition and the super-resolution method for the synthesis.…”
Section: State Of the Art In Synthetic Iris Data Generationmentioning
confidence: 99%
“…For instance, the General Data Protection Regulation (GDPR) in the EU has imposed restrictions. These regulations have led to either restricting or banning the collection of biometric datasets entirely [1], creating challenges for researchers and developers who rely on such data for their projects.…”
Section: Introductionmentioning
confidence: 99%
“…A notable direction in recent research is the attribute disentanglement technique, like what's seen in the DR-GAN framework [23], which can improve face recognition results. In parallel, there's a growing interest in using synthetic data to further push the boundaries of face recognition, both in terms of evaluating models and creating novel datasets [24], [25]. Our research builds on these advancements.…”
Section: Face Recognition and Synthetic Datamentioning
confidence: 99%
“…Gender classification from iris has been addressed in several publications [5][6][7][8], with different degrees of success [4]. Studies have revealed that most gender information is not actually contained in the iris, but outside of it [4,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%